Neutrophil-fibroblast crosstalk drives immunofibrosis in Crohn’s disease through IFNα pathway - Gavriilidis, Efstratios; Divolis, Georgios; Natsi, Anastasia-Maria; Kafalis, Nikolaos; Kogias, Dionysios; Antoniadou, Christina; Synolaki, Evgenia; Pavlos, Evgenios; Koutsi, Marianna A.; Didaskalou, Stylianos; Papadimitriou, Evangelos; Tsironidou, Victoria; et al. (Frontiers in Immunology, 2024)
Crohn's disease (CD) is characterized by chronic inflammation and intestinal fibrosis leading to lifelong complications. However, the disease pathogenesis remains elusive, and the therapeutic options are limited. Here, we investigated the interaction between neutrophils and intestinal fibroblasts in the development of CD immunofibrosis, a disease mechanism predisposing to inflammatory and fibrotic complications. Peripheral neutrophils, enriched neutrophil extracellular traps (eNETs), serum, primary intestinal fibroblasts (PIFs) and intestinal biopsies from CD, ulcerative colitis (UC) patients, and healthy individuals (HI), were studied. Transcriptome analysis of neutrophils, multi-cytokine profiling and cell-based functional assays at mRNA/protein level were performed. Compared to UC, PIFs from CD patients, independently to the presence of strictures, displayed a distinct pro-fibrotic phenotype characterized by negative Krüppel-like Factor-2 (KLF2) and increased cellular communication network factor-2 (CCN2) expression leading to collagen production. In both UC and CD, PIFs-derived IL-8 acted as a culprit chemoattractant for neutrophils in the intestine, where CD neutrophils were accumulated close to fibrotic lesions. Functionally, only CD neutrophils via eNETs induced a CD-like phenotype in HI PIFs, suggesting their fibrotic plasticity. High IFNα in serum and IFΝ-responsive signature in peripheral neutrophils were observed in CD, distinguishing it from UC. Moreover, CD serum stimulated the release of fibrogenic eNETs from neutrophils in an IFNα-dependent manner, suggesting the priming role of IFNα in circulating neutrophils. Inhibition of eNETs or JAK signaling in neutrophils or PIFs prevented the neutrophil-mediated fibrotic effect on PIFs. Furthermore, both serum IFNα levels and mRNA levels of key IFN signaling components in neutrophils were well-correlated with CD severity. This study reveals the important role of the IFNα/neutrophil/fibroblast axis in CD immunofibrosis, suggesting candidate biomarkers and putative therapeutic targets.